Growth of Chlorella pyrenoidosa on different septic tank effluents from rural areas for lipids production and pollutants removal. (November 2021) - Tan, Xiao-Bo; Wang, Lu; Wan, Xi-Ping; Zhou, Xiao-Ni; Yang, Li-Bin; Zhang, Wen-Wen; Zhao, Xian-Chao
Highlights: Different septic tank effluents were used for cultivating microalgae. Stressed conditions in mixed wastewater improved lipids content and saturation. Discharge of kitchen or laundry wastewater reduced biomass and lipids production. Abstract: Septic tank effluent from rural areas was an ideal medium for cultivating oleaginous microalgae. However, the characteristics of septic tank effluents varied greatly due to the different incoming wastewater, and bring uncertain risks for algal growth. In this study, an oleaginous microalgae was cultivated in septic effluents from different mixed wastewater. The results showed that the effluent from pure toilet wastewater was the best medium to achieve the highest biomass yield (1.68 g·L -1 ) and productivity (154.6 mg·L -1 ·d -1 ). In contrast, the discharge of kitchen or laundry wastewater reduced the biomass production by 50.5–79.1%. That caused much lower lipids production in effluents from mixed wastewater regardless of its high lipids content and saturation degree. The results suggest that the discharge of kitchen or laundry wastewater bring risks for biomass and lipids production, and should be separated from the toilet wastewater before entering into septic tank.